Traceless Staudinger Ligation for Biotinylation of Acetylated Thiol-Azido Heterobifunctional Linker and Its Attachment to Gold Surface - Senapati, Subhadip; Biswas, Sudipta; Zhang, Peiming (Current Organic Chemistry, 2018)
Background: Formation of Self-assembled monolayers (SAMs) is one of the most widely used methods to modify a surface to achieve the desired property. It is a very unique, yet simple method to produce highly ordered and stable monolayer on the surface. Adsorption of alkyl thiol to gold or other metal surface is one of the most commonly used methods for the SAM preparation. Biotin is a small molecule used extensively for labeling in biochemical research including bio-assays and biosensors, due to its strong affinity to proteins avidin (Ka 1015 M-1) and streptavidin (Ka 1013 M-1). Objective: Biotin-functionalized-PEG-PE-thiol linker is particularly useful for these studies carried out on surfaces. Current methods to synthesize biotinylated PEG-alkyl thiol linker are tedious because of the different reactive intermediate compounds involved in the process. We wanted to develop an alternative high-yielding synthetic route for the synthesis. Results: Here we report a scheme with improved yield for the synthesis of biotinylated PEG-alkyl thiol using the Traceless Staudinger Ligation. The synthesis can be carried out in large scale, making the process beneficial for industrial purposes. In-situ deprotection of the acetylated thiol allows simultaneous adsorption on a gold surface, resulting in stable, coordinated biotinylated monolayer. Monolayer formation was characterized by Fourier transform infrared spectroscopy (FTIR), contact angle and thickness measurement.
Keywords: traceless staudinger ligation